Dr. Виталий Жолтиков — Deep Plane Facelift - Жолтиков, Виталий (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Виталий Жолтиков, Russia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003396; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; russia